Analisis Dampak Pariwisata Berkelanjutan Terhadap Masyarakat Di Sekitar Wisata Kiara Artha Park Bandung - Faisal Hanafi Kaban; Dadan Ramdani (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the impact of sustainable tourism on the community surrounding Kiara Artha Park, Bandung, from a social, economic, and environmental perspective. The approach used in this study was descriptive qualitative, with data collection methods through direct observation and interviews with eleven visitors and several vendors operating in the park area. The results indicate that the park has a positive impact on social comfort, where visitors feel safe, calm, and have a space to interact and exercise. From an economic perspective, the park's presence has increased the income of small vendors and created new business opportunities. However, several obstacles remain, such as noise from surrounding traffic, facilities that are not accessible to people with disabilities, and a lack of informative signage. This study concludes that Kiara Artha Park reflects the principles of sustainable tourism, although it still needs strengthening in terms of inclusivity and environmental management. Future research is recommended to use a quantitative approach to measure economic impacts more thoroughly and involve more actors in the analysis.